Stent implantation of left main coronary artery stenosis in an infant: Effective long-term treatment? - Christian Paech; Ingo Dahnert; Frank Thomas Riede (Wolters Kluwer Medknow Publications, 2015)
Coronary artery stenosis is a rare phenomenon in children. Coronary stent implantation is generally not considered a standard treatment option due to technical difficulties and potential complications in this group of patients. Nevertheless, several pediatric cases reporting successful implantation with acceptable short-term experiences have been described. The following case presents a successful stent implantation for left main coronary artery (LMCA) stenosis early after surgery for anomalous left coronary artery from pulmonary artery (ALCAPA) at the age of 6 months. The excellent mid-term results and notably the procedure's potential as a long-term treatment in small children are highlighted. A 6-month-old infant underwent surgery for ALCAPA. Due to sudden postoperative deterioration, cardiac catheterization was performed. Coronary angiography revealed severe (90%) ostial LMCA stenosis. A PROMUS drug-eluting stent (Promus Element AL3.0 Χ 8 mm, Boston Scientific, Natick, Massachusetts, USA) was implanted. The procedure was performed without complications. Antiplatelet therapy with acetylsalicylic acid and clopidogrel was initiated. Subsequently, cardiac function improved slowly. Cardiac catheterization 3 years 8 months after stent implantation showed no restenosis with a proximal LMCA diameter still at the 50 th percentile for age. Neither were signs of heart failure reported at the last follow-up at 7 years of age. Presupposing normal growth, the implanted stent would thus provide sufficient myocardial perfusion with a LMCA lumen at the 40 th percentile at the age of 16 years. In selected cases, coronary stent implantation may be an effective mid- to long-term treatment of coronary artery stenosis even in very young children.